Performance Assessment Based on Added Value Management (Study of Cigarette Issuers in Indonesia) - Widiyati, Sri; Rikawati, Rikawati; Adhi, Nurseto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The research aims to evaluate the financial performance of PT Gudang Garam Tbk. and PT Hanjaya Mandala Sampoerna Tbk. for the 2018-2022 period based on Economic Value Added (EVA), Market Value Added (MVA), Financial Value Added (FVA). The data used is financial report data from the Indonesia Stock Exchange (BEI). The research results show that the EVA value at PT Gudang Garam Tbk. in 2018 and 2020 it was negative, while during 2019-2022 the EVA value was positive. A positive EVA value illustrates that the company's performance is good and able to create economic added value. MVA PT Gudang Garam Tbk. 2018 to 2020 is positive. Meanwhile, in 2021 and 2022 the MVA value is negative, which means the company has not been able to maximize shareholder wealth because resource management has not been optimal. FVA PT Gudang Garam Tbk. during 2018-2022 is positive. This can be interpreted as PT Gudang Garam Tbk. has created added financial value for the company. During 2018-2022 PT Hanjaya Mandala Sampoerna Tbk. having EVA, MVA and FVA is positive. This shows that the company can maximize shareholder wealth because resource management is optimal. Keywords: Financial Performance, Added Value, EVA, MVA, FVA